Physical-Self Declaration by University Students on Digital Media: A Gender Perspective - Lizama-Lefno, A (Centro de Informacion Tecnologica, 2021)
The primary objectives of this research study were to describe the “physical self affect on digital media” in Chilean university students and to examine patterns of digital and virtual behavior that reflect stereotypical gender mandates and behaviors. There were 324 women and 185 men surveyed on their “authentication of the physical self,” “definition or social status of the physical self,” and “definition of the photographic profile of the physical self.” The Stata V-14 program and the Mann-Whitney-Wilcoxon and Kruskal Wallis U tests were used to assess binary gender (male/female) and high school type (public, semi-private, private) where students had graduated. The results show that on digital media women tend to use their real names and surnames more frequently than men. Males and females have no issues stating their genders and sexual orientations. It is concluded that university students usually provide information that allows identifying them on digital media, with differences existing only by gender and not by high school type. © 2021. All Rights Reserved.